Gradients of the Drosophila Chinmo BTB-zinc finger protein govern neuronal temporal identity. - Zhu, S.; Lin, S.; Kao, C.F.; Awasaki, T.; Chiang, A.S.; Lee, T. (Cell, 2006)
Many neural progenitors, including Drosophila mushroom body (MB) and projection neuron (PN) neuroblasts, sequentially give rise to different subtypes of neurons throughout development. We identified a novel BTB-zinc finger protein, named Chinmo (Chronologically inappropriate morphogenesis), that governs neuronal temporal identity during postembryonic development of the Drosophila brain. In both MB and PN lineages, loss of Chinmo autonomously causes early-born neurons to adopt the fates of late-born neurons from the same lineages. Interestingly, primarily due to a posttranscriptional control, MB neurons born at early developmental stages contain more abundant Chinmo than their later-born siblings. Further, the temporal identity of MB progeny can be transformed toward earlier or later fates by reducing or increasing Chinmo levels, respectively. Taken together, we suggest that a temporal gradient of Chinmo (Chinmo(high) --> Chinmo(low)) helps specify distinct birth order-dependent cell fates in an extended neuronal lineage.